ASSESSMENT OF THE OPPORTUNITIES FOR THE USE OF WIND ENERGY IN THE SOUTHERN TERRITORY OF UZBEKISTAN - Uzakov, Gulom; Safarov , A.B.; Mamedov, R.A.; Davlonov, Kh.A. (Muqobil energetika, 2023)
The article presents the results of a study on assessing the potential of wind energy resources in the Kashkadarya region and identifying areas with high wind energy potential. It presents an analysis of scientific studies carried out around the world to assess the potential of wind energy resources and the efficient use of wind energy. Wind speeds at various points in the region were obtained from the Nasa Power Data Access Viewer (GIS). For a reliable assessment of the potential of wind energy resources at different heights, a two-parameter Weibull probability distribution function was used. The shape parameters k and the scale c of the Weibull distribution function are determined using an empirical method. Processing of the obtained data and mathematical modeling was done in the Matlab system. It was determined that the average wind speed in this region at a height of 10 m is (2.3-3.9) m/s, the average specific power is (20-40) W/m2, the average specific energy is (200-500) kWh/m2, and at a height of 100 m the average speed wind was (4-5.8) m/s, the average specific power was (113 – 253) W/m2, the average specific energy was (998.36-2208.03) kWh/m2. It was found that Mubarek and Mirishkor districts have a high potential for using wind energy. According to the results of the study, the annual gross (theoretical) wind energy potential of the region at a height of 100 m is 2296.15 billion kWh, the technical potential is 45.92 billion kWh. When providing consumers located far from the centralized power supply with uninterrupted and reliable electricity, wind energy can be used.